HBI1 acts downstream of ERECTA and SWR1 in regulating inflorescence architecture through the activation of the brassinosteroid and auxin signaling pathways. Issue 1 (1st September 2020) - Cai, Hanyang; Chai, Mengnan; Chen, Fangqian; Huang, Youmei; Zhang, Man; He, Qing; Liu, Liping; Yan, Maokai; Qin, Yuan
Summary: Inflorescence architecture critically influences plant reproductive success and crop yield, and it reflects the activity of the inflorescence meristem and pedicel length. In Arabidopsis thaliana, the ERECTA (ER) signaling pathway and the SWR1 chromatin remodeling complex jointly regulate inflorescence architecture by promoting the expression of the PACLOBUTRAZOL RESISTANCE ( PRE ) gene family. However, how PRE s regulate inflorescence architecture remains unclear. RNA‐sequencing and chromatin immunoprecipitation coupled with quantitative PCR analyses were performed. Genetic interactions between HOMOLOG OF BEE2 INTERACTING WITH IBH1 ( HBI1 ) and the SWR1‐ER‐MPK6 pathway in the control of inflorescence architecture were further studied. The present findings support that HBI1 functions downstream of PRE s in the SWR1 and ER pathways to regulate inflorescence architecture by promoting pedicel elongation. Specifically, it binds to the promoters of the brassinosteroid (BR) biosynthesis gene CYP85A2 and a series of auxin‐related genes, including auxin response factor ARF3, and promotes their expression. In turn, ARF3 can also bind to auxin signaling genes as well as CYP85A2 to activate their expression and promote pedicel elongation. Our study provides evidence that inflorescence architecture regulation by SWR1 and ER involves the HBI1 regulatory hub and its activation of both the BR and auxin hormone pathways.